2017
DOI: 10.4103/ijpsym.ijpsym_61_17
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Opioid Substitution Therapy in a Tertiary Care Center of Eastern India

Abstract: Background: Opioid substitution therapy (OST) is an evidence-based intervention for opiate-dependent persons that replaces illicit drug use with medically prescribed, orally administered opiates such as buprenorphine and methadone. OST reduces HIV risk behaviors and harms associated with injecting opioid. Most of the evidence for OST effectiveness has been generated in middle- and high-income countries where programs are mostly located in dedicated health-care settings; evidence regarding the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Participants had a median age of 28.5 years (IQR 26.6-32.3) and were predominantly male (58%), heterosexual (91%), had completed secondary education (87%) and were currently (76%) or recently (92%) homeless as indicated by Table 1. The median reported starting age of injecting drug use was 22 years (IQR [19][20][21][22][23][24][25][26]. The majority of participants did not use other (non-injection) drugs (85%) or alcohol (64%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants had a median age of 28.5 years (IQR 26.6-32.3) and were predominantly male (58%), heterosexual (91%), had completed secondary education (87%) and were currently (76%) or recently (92%) homeless as indicated by Table 1. The median reported starting age of injecting drug use was 22 years (IQR [19][20][21][22][23][24][25][26]. The majority of participants did not use other (non-injection) drugs (85%) or alcohol (64%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, access to harm reduction services that included access to housing, food, and naloxone nasal spray may improve survival and adherence to medical therapies [12]. Outreach and mobile medical services targeting the homeless and drug using population could assist in introducing this population to medical services; however, evidence-based interventions for low-to-middle income countries (LMIC) are limited [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…24 Another study from India also reported a lower dosage of OST similar to the current study. 25 Another observation was a decreasing trend of comorbid substance use disorders like cannabis and alcohol. Could this be alluded to the fact that there is difficulty in procuring these substance (as alcohol is considered a taboo in a conservative Muslim society like Kashmir) or more adolescents experimenting with opioids directly, only future studies could make us wiser?…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of social, economic, and psychological factors that influence ORT availability and retention rates. Studies have estimated that up to 15% of individuals with OUD are on ORT [ 37 , 43 , 44 ]. Although it is widely used for dependence and addiction, there remains an existing social stigma, preconceived negative views, and a general lack of awareness that ORT is a medically prescribed and evidence-based method to manage OUD [ 37 , 40 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…There are a variety of social, economic, and psychological factors that influence ORT availability and retention rates. Studies have estimated that up to 15% of individuals with OUD are on ORT [37,43,44].…”
Section: Treatment Availability and Retentionmentioning
confidence: 99%